Synthesis of substituted tetrahydro-1H-xanthen-1-ones and xanthenes - Patil, M. L.; Borate, Hanumant B. (Journal of Chemical Research, 2005)
A short and an efficient methodology for the synthesis of substituted tetrahydro-1H-1-xanthenones and xanthenes is described.
Keywords: balanol; diarylmethanes; tetrahydro-1H-xanthen-1-ones; Xanthenes

Simple and efficient synthesis of thysanone methyl ether - Bulbule, Vivek J.; Koranne, Priti S.; Deshpande, Vishnu H.; Borate, Hanumant B. (Tetrahedron, 2007)
The synthesis of thysanone methyl ether is achieved by employing semivioxanthin methyl ether, which in turn is prepared by the tandem Michael addition of an anion of orsellinate to a substituted dihydropyrone. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: human pathogen; Michael addition; orsellinate derivative; semivioxanthin

Synthesis and evaluation of 4/5-hydroxy-2,3-diaryl(substituted)-cyclopent-2-en-1-ones as cis-restricted analogues of combretastatin A-4 as novel anticancer agents - Gurjar, Mukund K.; Wakharkar, Radhika D.; Singh, Anu T.; Jaggi, Manu; Borate, Hanumant B.; Shinde, Popat D.; Verma, Ritu; Rajendran, Praveen; Dutt, Sarjana; Singh, Gurvinder; Sanna, Vinod K.; Singh, Manoj K.; et al. (Journal of Medicinal Chemistry, 2007)
A new series of 2,3-diaryl-4/5-hydroxy-cyclopent-2-en-1-one analogues replacing the cis double bond of combretastatin A-4 (CA-4) by 4/5-hydroxy cyclopentenone moieties was designed and synthesized. The analogues displayed potent cytotoxic activity (IC50 < 1 mu g/mL) against a panel of human cancer cell lines and endothelial cells. The most potent analogues 11 and 42 belonging to the 5-hydroxy cyclopentenone class were further evaluated for their mechanism of action. Both of the analogues led to cell cycle arrest at G2/M phase and induced apoptosis in endothelial cells. Antitubulin property of 42 was superior to 11 and comparable to CA-4. The compound 42 had better aqueous solubility, metabolic stability, and pharmacokinetic profile than CA-4 and also demonstrated significant tumor regression in the human colon xenograft model. Our data suggests that cis-restricted analogues of CA-4 are a new class of molecules that have the potential to be developed as novel agents for the treatment of cancer.

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Short synthesis of 3,6-disubstituted N-2-thienyl/aryl-indoles - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Maujan, Suleman R. (Tetrahedron Letters, 2009)
A short synthetic strategy for 3,6-disubstituted-N-2-thienyl/aryl-indoles, involving reaction of substituted 2,4-difluoro/dichloro-styrene epoxide with substituted 2-formylaminothiophenes or substitued N-formylanilins in the presence of a base followed by treatment with an acid, has been developed The method was applied for the synthesis of a number of indoles with a variety of substitutents at 1, 3, and 6 positions of the indole moiety. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: Formylaminothiophene; Gewald synthesis; Indole; Styrene epoxide

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein

Synthesis of substituted 2,6-dicyanoanilines and related compounds. a review - Borate, Hanumant B.; Kudale, Ananada S.; Agalave, Sandip G. (Organic Preparations and Procedures International, 2012)

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (MedChemComm, 2015)
A number of thieno[2,3-d]pyrimidin-4(3H)-ones were designed, synthesized and screened against Mycobacteria as a part of our program to develop new antitubercular agents. It was observed that some of the compounds have significant antimycobacterial activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743). The active compounds were studied for cytotoxicity against four cell lines and were found to be non-cytotoxic. The results showed that compounds 13b and 29e were found to exhibit very good antimycobacterial activity (MIC in the range of 6-8 mu M) and the thienopyrimidinones as a class have potential to be developed as antitubercular agents.

Synthesis and evaluation of thieno[2,3-d]pyrimidin-4(3H)-ones as potential antitubercular agents (vol 6, pg 2209, 2015) - Borate, Hanumant B.; Annadate, Ritesh A.; Vagh, Sandip S.; Pisal, Mahesh M.; Deokate, Sagar B.; Arkile, Manisha A.; Jadhav, Nandadeep J.; Nawale, Laxman U.; Sarkar, Dhiman (Medchemcomm, 2016)

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocycl- yl-2,6-dicyanoanilines - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Dipak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2017)
Synthesis of 3,4,5-triheterocyclyl-2,6-dicyanoanilines, starting from heterocyclic aldehydes and 1,2-diheterocycle-substituted ethanones, is described. 2,6-Dicyanoanilines with one or two heterocyclic substituents have also been synthesized. It was found that some of these molecules have selective cell-staining properties useful for cell imaging applications. The compounds 1g, 10f and 11 were found to stain cytoplasm of the cells in contact but not the nucleus while the compound 12 showed affinity to apoptotic cells resulting in blue fluorescence. The cell imaging results with compound 12 were similar to Annexin V-FITC, a known reagent containing recombinant Annexin V conjugated to green-fluorescent FITC dye, used for detection of apoptotic cells. These compounds were found to be non-cytotoxic and have potential application as cell imaging agents.

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocyclyl-2,6-dicyanoanilines (vol 27, pg 979, 2017) - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Deepak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2021)